2020
DOI: 10.1016/j.cej.2020.124599
|View full text |Cite
|
Sign up to set email alerts
|

An effective combination reaction involved with sputtered and selenized Sb precursors for efficient Sb2Se3 thin film solar cells

Abstract: Sputtering followed by post annealing is extensively used for fabrication of copper indium gallium selenide (CIGS), copper zinc tin sulfide (CZTS) and copper zinc tin sulfur selenide (CZTSSe) thin film solar cells. In this work, Sb 2 Se 3 as an emerging alternative absorber was fabricated by an effective combination reaction of annealing sputtered Sb metallic precursors under Se vapor. Self-assembled growth of Sb 2 Se 3 thin films consist of large grains that across the whole films have been successfully fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…Also, TAS has been widely used in Sb 2 X 3 to measure the defect information, including both deep-and shallow-level defects. [62][63][64][65][66] In order to obtain the defect density and energy level position within the bandgap in a semiconductor, TAS measurements at various temperatures are usually used. Hu et al systematically identified and characterized the defects in Sb 2 Se 3 solar cells by TAS.…”
Section: Defect-assisted Recombination In Sb 2 X 3 Solar Cellsmentioning
confidence: 99%
“…Also, TAS has been widely used in Sb 2 X 3 to measure the defect information, including both deep-and shallow-level defects. [62][63][64][65][66] In order to obtain the defect density and energy level position within the bandgap in a semiconductor, TAS measurements at various temperatures are usually used. Hu et al systematically identified and characterized the defects in Sb 2 Se 3 solar cells by TAS.…”
Section: Defect-assisted Recombination In Sb 2 X 3 Solar Cellsmentioning
confidence: 99%
“…In the last few years, antimony selenide (Sb 2 Se 3 ) semiconductor has received considerable attention as an attractive absorber material in the thin‐film heterojunction photovoltaic device due to its high absorption coefficient (>10 5 cm −1 ), favorable energy bandgap (1–1.2 eV), reasonable carrier mobility, low toxicity, earth‐abundant constituents, inexpensive, low temperature fabrication process, and excellent stability. [ 20–30 ] In the previous works, several experimental [ 20–23,27,31–40 ] and theoretical [ 41–47 ] studies on improving the performances of the Sb 2 Se 3 ‐based solar cells have been reported. There have been numerous experimental Sb 2 Se 3 ‐based heterojunction solar structures, including TiO 2 /Sb 2 Se 3 , [ 18 ] TiO 2 /Sb 2 Se 3 /CuSCN, [ 31 ] CdS/Sb 2 Se 3 , [ 23,32,33,35,36,38–40 ] CdS/Sb 2 Se 3 /PbS, [ 34 ] and CdS/Sb 2 Se 3 /CuSCN, [ 37 ] described to achieve excellent photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–6 ] However, poor stability is still a barrier on their road to commercialization. At the same time, the emerging binary Sb‐based compound solar cell has its own advantages and challenges, [ 7–9 ] and its efficiency is currently approaching 10%. [ 10 ] As a substitute in the large‐scale thin‐film production technology of Cu(In,Ga)Se 2 (CIGS), kesterite thin‐film solar cells including Cu 2 ZnSn(S,Se) 4 (CZTSSe) have the same advantages and device structures.…”
Section: Introductionmentioning
confidence: 99%